Ernst Tugendhat and Leo Strauss:: The Use and Abuse of Socratic Ignorance - Altman, William (Dia-noesis: A Journal of Philosophy, 2024)
A comparison of the way Leo Strauss and Ernst Tugendhat treat Socratic Ignorance reveals a political gulf dividing these two important thinkers. This comparison is based on Tugendhat’s Selbstbewußtsein und Selbstbestimmung (1979) and two essays of Strauss, the pre-War “Religiöse Lage der Gegenwart” (1930) and the post-War “How to Study Spinoza’s Theologico-Political Treatise” (1948). While Tugendhat points to Socratic Ignorance as a remedy against political extremism, Strauss illustrates how it can be made to subserve it. And while Tugendhat assumes that the threat posed by National Socialism has been checked, Strauss demonstrates that it still remains an ongoing danger.